Ethanolic extract of ocimum kilimandscharicum linnleaves: phytochemical and in vitro pharmacological activity - N, Yamini; s, Lahari; V, Phani deepthi (International Journal of Indigenous Herbs and Drugs, 2021)
Using an in vitro model, the anti-thrombolytic efficacy of ethanolic extracts of Ocimum kilimandscharicum Linn was investigated. The researchers discovered that different concentrations of the extract had significant anti-thrombolytic activity in a dose-dependent manner , which was comparable to a standard drug. As a result of the presence of flavonoids and polyphenols in the plant extract, it can be concluded that it has a promising future in the treatment of thrombosis. This knowledge will be useful in the clinical development of thrombolytic therapeutics by identifying more potent anti-thrombolytic principles from natural resources..